Effects of Customer Relationship Marketing, Service Quality, and Product Excellence On Customer Value and Its Effects on Satisfaction and Loyalty of PT. Bank Syariah Mandiri Customers - Riduan Mas’ud; Muhamad Yusup (International Journal of Islamic and Social Sciences (ISOS), 2021)
This research aims to determine the effects of customer relationship marketing, service quality, and product excellence on customer value, and its effects on the satisfaction and loyalty of PT. Bank Syariah Mandiri customers in West Nusa Tenggara (NTB). The research method used survey method involving 250 people as the samples taken in sensus manner. The data collection used questionnaire and the data analysis used Structural Equation Modelling (SEM). Results of the research indicate that each factor and construct affect recursively, namely customer relationship marketing, service quality, and product excellence affecting on the customer value; the customer value affects on the customer satisfaction, and the customer satisfaction affects on the customer loyalty.